Analysis the Hidden Advantages of Written Pretests for Student Intelligence - Taufik, Ali; Saidi, Suid; Apendi, Tatang (Universitas Malikussaleh, 2019)
This research starts from the concept of oral pretest, which is almost always monotonous, often carried out by teachers or lecturers when conducting teaching and learning activities in front of the class so that oral pretest is only considered a question that is not too important by students.The author tries to do research using written pretest, the aim is to improve, sharpness, thinking patterns, understanding, and intelligence. This can be done for all students as a whole, with only around 10-15 minutes, when discussions about new lessons begin, it turns out that there is a significant increase in students' understanding and intelligence